Preventing surface spillage of toxic liquids due to seal failure of injection wells - Prihod’ko, N. K.; Latyshev, V. E. (Atomic energy (New York, N.Y.), 2013)
Biologically hazardous liquid wastes (industrial wastes), for example, radioactive or containing highly toxic chemical substances, are now commonly disposed of deep underground [1, 2]. Ordinarily, toxic liquid industrial wastes are pumped under excess pressure through injection wells with wellheads designed for the appropriate working pressure. Such wellheads are subject to seal failure while the injection well is in operation. In this situation, toxic liquid will spill onto the surface, as a result of which soil and ground waters will become contaminated. Urgent technological actions must be taken in order to prevent or minimize the harm done to the environment. Running a packer into the well in order to cover the flow or other technical actions at excess pressure are ruled out because such actions will result in not only the contamination of the well-head site but also the maintenance crew. In the present communication, we describe a simple and safe method of preventing environmental contamination during accidental seal failure of an injection well.